Posthumous Justice: A Socio-Legal Interpretation of Rights of The Dead - P. C., Harigovind; P. S., Rakesh (Journal of Law and Legal Reform, 2025)
Rights have always been regarded as a subject matter of personhood. At the same time, the understanding of personhood has extended beyond the limit of living human beings. Today, the world has witnessed the transgression of the concept to non-human and even artificial entities. The core value of such recognition is to confer rights and thereby ensure their legitimate protection. To this conundrum comes a dead body, especially that of a human being. This paper attempts to delve into the aspects of personhood, the rights of the dead and the need of positive state action for protecting a person’s dignity even after the end of their natural life. The discussion examines these aspects in the wake of various actions performed on the dead, which would otherwise be deemed offensive if the person was alive.